In vivo analysis of post space sealing with different adhesive materials Análise in vivo do selamento do canal protéico com diferentes materais adesivos - Carlos Alexandre Souza Bier; José Antônio Poli de Figueiredo; Álvaro Della Bona; Patrícia Maria Poli Kopper; José Roberto Vanni; Simone Bopp (University of São Paulo, 2003)
This in vivo study analyzed the sealing ability of two adhesives in post spaces, cyanoacrylate (Super Bonder® - Henkel Loctite Adesivos Ltda., Itapevi, SP, Brazil) and ScotchbondTM Multi-Purpose (3M Dental Products, St. Paul, MN, USA), testing the hypothesis that their use would result in a decreased leakage through the remaining filling material. Forty extracted premolars (80 root canals) of dogs were used. The root canals were cleaned, shaped and filled by the lateral condensation technique using Sealer 26TM. The post space was created removing two thirds of the filling material within the root canal. The canals were randomly divided in three groups, which were treated as follows: Group A received the ScotchbondTM Multi-Purpose adhesive system; for Group B the cyanoacrylate adhesive, Super BonderTM, was employed; and no adhesive was applied into the post space for Group C (control group). A glass ionomer provisional restoration was placed allowing the sealer to set for 72 hours. Then the restoration was removed and the root canal was exposed to the oral environment for 45 days. The dogs were then killed and their jaws were removed. The post spaces were filled with India ink and the teeth were restored for 96 hours. Afterwards, the teeth were extracted and the roots were sectioned at the furcation for allocation to their specific groups. The teeth were turned transparent and the quantitative analysis of leakage was performed using light microscopy. The results showed no significant differences between groups, rejecting the initial hypothesis. Leakage occurred in a great extent in all specimens. Therefore, sealing post spaces with the adhesives used in this study was not an effective method to prevent microleakage. Esse estudo in vivo analisou a capacidade de selamento do canal protético com dois adesivos, o Super Bonder® (Henkel Loctite Adesivos Ltda., Itapevi, SP) e o Scotchbond® Multi-Purpose (3M Dental Products, St. Paul, MN, EUA), testando a hipótese de que a aplicação desses adesivos resulta em menor infiltração de corante no material obturador remanescente. Quarenta dentes pré-molares (80 canais) de cães foram obturados pela técnica da condensação lateral usando o cimento endodôntico Sealer 26®. O canal protético foi preparado removendo-se 2/3 da obturação do canal radicular. Os canais preparados foram distribuídos, aleatoriamente, em três grupos: no grupo A, foi realizado o selamento do canal protético com o adesivo dentinário; no grupo B, esta impermeabilização foi realizada com o Super Bonder®; e no grupo C, controle, não foi aplicado qualquer material às paredes do canal protético. Os dentes foram selados, provisoriamente, com cimento de ionômero de vidro por 72 horas, objetivando a presa do cimento endodôntico. Removido o selamento coronário, os canais ficaram expostos ao meio bucal por 45 dias, quando os cães foram mortos e os maxilares removidos. Tinta nanquim foi colocada no canal protético e os dentes foram selados por 96 horas. Depois de extraídos, os dentes foram seccionados na região da furca e cada raiz alocada em seu respectivo grupo. Feita a diafanização, foi realizada a análise quantitativa da infiltração do corante com lupa esteroscópica. Os resultados mostraram não haver diferenças entre os três grupos experimentais, negando a hipótese inicial. Houve infiltração do corante no remanescente obturador de todas as raízes analisadas.